Pengaruh Ketebalan Woven Fusible Interfacing Terhadap Kualitas Produk Lengan Spiral Pada Blus Berbahan Taffeta - JAILANI AZIZ, FIQIH; ENDANG KARYANINGRUM, ANNEKE (Universitas Negeri Surabaya, 2019)
Abstract Interfacing is an inside layer to supporting , strong holding, and keeping the form of a cloth or dress. Interfacing is applied on some certain part for example pocket, collar neck, cuff, and many more. Its function is to form and give a volume on the arm. this research is for knowing the thickness effect of wove fusible interfacing against spiral arm product quality on the blouse using Taffeta as the material, based on the flatness of spiral arms aspect, the form stability, volume, and the length of the spiral arms which its function to know the result of the best spiral arms from the appliance of the 3 type of woven fusible interfacing on the blouse that using Taffeta as the material, based on the flatness of spiral arms aspect, the form stability, volume, and the length of the spiral arms. This is an experimental research by using observation method in data gathering. By observing the object and the observer filling the questionnaire by check listing (?) on the observation form. The data analysis that being used in this research is non-pramectic kruskal wallis test with some help from the SPSS 23 program and P ? 0,05. The result of the test is showing that (1) there is an influence on the woven fusible interfacing against four aspects on the quality of the spiral arm product on the blouses using Tafetta as the material which is the flatness of the spiral arm aspect, the stability of the spiral arm form aspect, the volume of spiral arm aspect and the length of the spiral arm aspect. (2) the result in the quality of the spiral arm product as the best result is from woven fusible interfacing type M70 with 0,56 mm as the thickness. keywords : : spiral arm, blouse, Taffeta fabric, woven fusible interfascing type M10, M32, dan M70.